Macroeconometric evaluation of active labour market policies in Austria - Wolfgang Dauth; Reinhard Hujer; Katja Wolf (European Regional Science Association (ERSA), 2011)
The analysis of active labour market policies (ALMP) at the macroeconomic level measures net effects on labour market outcomes. These net effects consist of direct treatment effects on participants as well as indirect effects on non-participants and on the economy as a whole, e.g. deadweight, substitution and displacement effects. This paper contributes to the empirical studies of macroeconometric evaluation of ALMP by considering the regional effects on both the matching process and the job-seeker rate. This joint view permits us to draw conclusions on how ALMP achieves the goals set by policy makers. To this end, we use an exclusive data set on Austrian job-seekers in the years 2001 to 2007 and employ contemporaneous GMM and quasi-ML estimators to take into account both the simultaneity of ALMP and spatial interrelations between employment office districts. The empirical results indicate that a large number of participants in job schemes in the non-profit sector, wage subsidies, and apprenticeships cause particularly favourable effects on the regional matching function and the job-seeker rate.
Keywords: 330